IL-1RN VNTR Polymorphism in Adult Dermatomyositis and Systemic Lupus Erythematosus - Zornitsa Kamenarska; Gyulnas Dzhebir; Maria Hristova; Alexey Savov; Anton Vinkov; Radka Kaneva; Vanio Mitev; Lyubomir Dourmishev (Dermatology Research and Practice)
Polymorphisms in the cytokine genes and their natural antagonists are thought to influence the predisposition to dermatomyositis (DM) and systemic lupus erythematosus (SLE). A variable number tandem repeat (VNTR) polymorphism of 86 bp in intron 2 of the interleukin-1 receptor antagonist (IL-1RN) gene leads to the existence of five different alleles which cause differences in the production of both IL-1RA (interleukin-1 receptor antagonist) and IL-1β. The aim of this case-control study was to investigate the association between the IL-1RN VNTR polymorphism and the susceptibility to DM and SLE in Bulgarian patients. Altogether 91 patients, 55 with SLE and 36 with DM, as well as 112 unrelated healthy controls, were included in this study. Only three alleles were identified in both patients and controls ((1) four repeats, (2) two repeats, and (3) five repeats). The IL-1RN*2 allele (P=0.02, OR 2.5, and 95% CI 1.2–5.4) and the 1/2+2/2 genotypes were found prevalent among the SLE patients (P=0.05, OR 2.6, and 95% CI 1–6.3). No association was found between this polymorphism and the ACR criteria for SLE as well as with the susceptibility to DM. Our results indicate that the IL-1RN VNTR polymorphism might play a role in the susceptibility of SLE but not DM.